Agriculture 4.0 - A state of the art review focused on electric mobility - Weisbach, Michéle; Fechtner, Heiko; Popp, Alexander; Späth, Utz; Schmülling, Benedikt (Revista Ciência Agronômica, 2021)
In its endeavor to conserve resources and create a more environmental-friendly agriculture, the 4th agricultural revolution now underway needs innovative methods and new technologies to achieve a more sustainable farming industry. In addition to the different methods and applications, subsumed under the term agriculture 4.0, this article focuses on the areas in which the discipline of electric mobility is becoming more and more important. Therefore, the two superordinate categories “family” and “industrial” farming were considered separately to compare technical approaches and solution which are currently in use or conceivable in the future.